Trinity [large type] : military war dog - Kendig, Ronie (A breed apart series, 2013)
A year ago in Afghanistan, Green Beret Heath Daniels' career was destroyed. Along with his faith. Forced to the sidelines by a medical discharge, he and his military war dog, Trinity, now train other dogs and their handlers. But military intelligence officer Darci Kintz has been captured while secretly tracking the Taliban. Only one dog can handle the extreme conditions to save her. Only one man can handle Trinity. Time is running out.